Tyrosine kinase inhibitors in chronic myeloid leukaemia and emergent cardiovascular disease. Issue 8 (8th January 2021) - Leong, Darryl; Aghel, Nazanin; Hillis, Christopher; Siegal, Deborah; Karampatos, Sarah; Rangarajan, Sumathy; Pond, Gregory; Seow, Hsien
Abstract : Objectives: (1) Describe how the risk of major adverse cardiovascular events (MACE) in individuals with chronic myeloid leukaemia (CML) has evolved; (2) evaluate the risk of MACE associated with the prescription of different CML tyrosine kinase inhibitors (TKI). Methods: A population-based retrospective study including all patients (n=4238) diagnosed with CML in Ontario, Canada between 1986 and 2017 and and age-matched and sex-matched individuals who received healthcare but who did not have CML (controls: n=42 380). The cohort was divided into those entering before 2001 vs from 2001 onwards (when TKIs were introduced). We developed competing risks models to compare time-to-event in CML cases versus controls. We adjusted for baseline comorbidities and present subdistribution HRs and 95% CIs. The relationship between TKI use and MACE was assessed by logistic regression. Results: Before 2001 and from 2001 on, patients with CML had a higher crude incidence of MACE than patients without CML (19.8 vs 15.3 and 20.3 vs 12.6 per 1000 person-years, respectively). After adjustment for cardiovascular risk factors, patients with CML had a lower subdistribution hazard for MACE (0.59, 95% CI 0.46 to 0.76) before 2001; but from 2001, the adjusted subdistribution HR for MACE (1.27, 95% CI 0.96 to 1.43) was similar to age-matched and sex-matched patients. The incidence (9.3 vs 13.8 per 1000 person-years) and subdistribution hazard for cardiovascular death (0.43, 95% CI 0.36 to 0.52) were lower in patients with CML than controls before 2001. From 2001 on, the incidence (6.3 vs 5.4 per 1000 person-years) and subdistribution hazard for cardiovascular death (0.99, 95% CI 0.84 to 1.18) were similar to age-matched and sex-matched patients without CML with a higher risk of cerebrovascular events (8.6 vs 5.6 per 1000 person-years; 1.35, 95% CI 1.00 to 1.83) and peripheral arterial events (6.9 vs 3.0 per 1000 person-years; 1.66 95% CI, 1.15 to 2.39) in patients with CML than patients without CML. Compared with imatinib, there was no difference in the risk of MACE among those prescribed dasatinib (OR 0.67, 95% CI 0.41 to 1.10) or nilotinib (OR 1.22, 95% CI 0.70 to 1.97). Conclusions: In a contemporary CML population, the risk of MACE and cardiovascular death is at least as high as among age-matched and sex-matched patients without CML and may be higher for cerebrovascular and peripheral arterial events. No difference in the risk of MACE between imatinib, dasatinib and nilotinib was observed.